2010
DOI: 10.1177/147323001003800124
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cytokine Balance on the Third Postpartum Day is Not Affected by the Mode of Delivery after Healthy Pregnancies

Abstract: Previous reports have suggested that delivery is associated with the induction of inflammatory cytokines. The present study was designed to investigate whether increased cytokine production was present on postpartum day 3 after a normal pregnancy and whether any changes were associated with the mode of delivery. In total, 33 pregnant women were enrolled; 18 delivered vaginally and 15 underwent an elective caesarean section (C-section). The levels of 17 cytokines and growth hormones were measured at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
1
1
Order By: Relevance
“…This assumption is not supported by unaltered levels of IL‐6, a major trigger of hepcidin synthesis. (Of note, in a previous work we found somewhat decreasing IL‐6 following CS; 10 this discrepancy with the current study is probably due to use of another IL‐6 test with different sensitivity.) However, hepcidin levels following CS were greater than after vaginal delivery, suggesting that some factor associated with CS may contribute to hepcidin increase.…”
Section: Discussioncontrasting
confidence: 99%
“…This assumption is not supported by unaltered levels of IL‐6, a major trigger of hepcidin synthesis. (Of note, in a previous work we found somewhat decreasing IL‐6 following CS; 10 this discrepancy with the current study is probably due to use of another IL‐6 test with different sensitivity.) However, hepcidin levels following CS were greater than after vaginal delivery, suggesting that some factor associated with CS may contribute to hepcidin increase.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies have reported that the mode of delivery and parturition are associated with an increase in proinflammatory cytokines [22]. Uteroplacental hypoxemia caused by SA may result in inflammatory changes in the placenta and induce the release of proinflammatory cytokines and selectins.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos têm demonstrado que a infecção intrauterina pode provocar a interrupção da gravidez, bem como o aumento de secreção de citocinas 55 .Grande parte dos partos prematuros é desencadeado pelo aumento do estado pró-inflamatório do organismo, causado por infecções bacterianas56 .A associação na produção de citocinas e o hormônio do crescimento em amostras do soro de gestação de baixo risco, colhidas antes da anestesia, três dias após o parto vaginal e três dias após a operação cesariana eletiva, mostram que IL-6 e a IL-8 diminuíram significativamente após o parto, e apenas a interleucina 7 ficou alterada em pacientes que foram submetidas a operação cesariana. As pacientes não apresentaram aumento do risco de resposta inflamatória prolongada, independente se submetidas à operação cesariana ou se evoluíram para parto vaginal57 .Citocinas foram pesquisadas em parturientes saudáveis que evoluíram para parto vaginal e naquelas que foram submetidas à operação cesariana eletiva. Verificou-se que parturientes que evoluíram para parto vaginal tiveram aumento na produção de várias citocinas, como a IL-6 e a IL-1β e TNF, as quais estão associadas com a imunidade neonatal por meio de diferentes mecanismos17 .Outro estudo avaliou a participação da IL-6 na resposta de infecção intrauterina, em gestantes em trabalho de parto prematuro, colhido no líquido amniótico de gestantes no terceiro trimestre, em trabalho de parto a termo e trabalho de parto pré-termo.…”
unclassified